ANALISIS STUKTUR TEKS ANEKDOT DARI CERITA “SI KABAYAN” - Ryan Septian Wicaksono; Dina Siti Mardiah; Rochmat Tri Sudrajat (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The purpose of this study is to describe the learning of analyzing anecdotal text from the aspect of its structure in west java folklore that is Kabayan. The type of this research is descriptive qualitative. The data in the study were analyzed by an analytical technique in the form of analyzing the structure of the anecdotal text in Kabayan story. Structure of anecdote text is Abstract, Orientation, Crisis, Reaction, and Coda. The researchers analyzed the anecdotal text structure of the text entitled Si Kabayan. Descriptive research can be used to answer research questions (not hypothesized) and test hypotheses (hypothesized). In this case, the hypothesis in the test is a Descriptive hypothesis which states the estimation of certain characteristics.